2015
DOI: 10.1117/1.jbo.20.5.051043
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5-aminolevulinic acid-conjugated gold nanoparticles for photodynamic therapy of cancer

Abstract: There are three possible mechanisms for 5-aminolevulinic acid (5-ALA) conjugated gold nanoparticles (GNPs) through electrostatic bonding for photodynamic therapy (PDT) of cancer: GNPs delivery function,singlet oxygen generation (SOG) by GNPs irradiated by light, and surface resonance enhancement (SRE) of SOG. Figuring out the exact mechanism is important for further clinical treatment. 5-ALA-GNPs and human chronic myeloid leukemia K562 cells were used to study delivery function and SOG by GNPs. The SRE of SOG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 54 publications
1
34
1
Order By: Relevance
“…Moreover, higher cytotoxic effects resulted from irradiation by the 650‐nm laser than by the 808‐nm laser, and this was observed for both types of Pt NPs. TEM showed that the structure, size, and shape of both NPs types are very similar; however, it is known that the enhancement of local electromagnetic field around a platinum NP depends not only on the NP size, but also on the light wavelength used . Moreover, in the laser irradiated cells cultured with Pt NPs, a correlation between the synthesis method and cytotoxicity effect was noted.…”
Section: Resultscontrasting
confidence: 50%
“…Moreover, higher cytotoxic effects resulted from irradiation by the 650‐nm laser than by the 808‐nm laser, and this was observed for both types of Pt NPs. TEM showed that the structure, size, and shape of both NPs types are very similar; however, it is known that the enhancement of local electromagnetic field around a platinum NP depends not only on the NP size, but also on the light wavelength used . Moreover, in the laser irradiated cells cultured with Pt NPs, a correlation between the synthesis method and cytotoxicity effect was noted.…”
Section: Resultscontrasting
confidence: 50%
“…His group developed a new modality combined PDT with photothermal therapy (PTT) mediated by gold nanoparticles (GNPs), to realize the dual‐modal therapy. They found that GNPs could improve the singlet‐oxygen generation of photosensitizer conjugated on the surface due to its local field enhancement (LFE) effect through both theory calculation and experimental results . They utilized a new photochemical strategy called photochemical internalization, which was modified from PDT, to noninvasively disrupt the endosome by singlet oxygen and successfully released the entrapped drugs into the cytoplasm .…”
Section: Selected Research Achievementsmentioning
confidence: 99%
“…Since Geddes et al. firstly reported the a 3‐fold enhancement of 1 O 2 generation by Rose Bengal (RB) in the presence of silver island films (SiFs), various studies using Ag, Au, Zn and Ni nanoparticles for 1 O 2 enhancement have been performed, and this approach may well prove to be of significance for 1 O 2 ‐based clinical therapy . The fluorescence emission can also be enhanced by orders of magnitude, facilitating imaging of the nanoparticle localization as well as photobleaching‐based dosimetry (see Section ).…”
Section: Strategies For Enhanced Photosensitized 1o2 Generationmentioning
confidence: 99%